Deteksi Kandungan DNA Babi dalam Produk Olahan Daging dengan Metode Real Time-Polymerase Chain Reaction: Detection the DNA Content of Pig in Processed Meat Products using the Real Time-Polymerase Chain Reaction Method - Aditia, Kay Almira; Fauziyyah, Athiefah (Jurnal Teknologi dan Mutu Pangan, 2023)
Changes in the community's paradigm regarding food security, lifestyle, and consumption patterns healthy, and meeting the needs of animal protein makes the government realize it provision of processed meat products that are safe, healthy, whole and halal. Related problemsfood safety and halal in processed meat products, namely the addition of orsubstitution of pork and other ingredients containing pork components. This matter creates a sense of insecurity and public concern regarding religious beliefs, culture, and health problems. The research aims to determine the content of DNA pork in processed meat products, namely shredded, meatballs, beef burgers, and sausages with detecting the content of pig DNA and its derivative components, as well as knowing the performance of the kit reagent (mastermix) using the RT-PCR method or specific DNA amplification techniques species because it has fast analysis time, sensitivity, specificity, and accuracy tall. The processed meat product samples analyzed had an average concentration of DNA between 6.20 ng/µl – 126.47 ng/µl and the average DNA purity value (A260/280) between 1.754 – 1.891. The results of pig DNA detection by RT-PCR method showed that in samples of processed meat products did not detect pig DNA content supported by performance kit (mastermix) that works optimally. The increase in the curve only occurs in the positive control of extracted pork with a Ct value of 18.30 and a positive control from the kit with Ct value of 29.95.